Shaping health: conducting a community health needs assessment in culturally diverse peripheral population groups - Nosaiba Rayan-Gharra; Marganit Ofir-Gutler; Sivan Spitzer (International Journal for Equity in Health, 2022)
Abstract Introduction The impact of social determinants on health status and outcomes has been widely established. However, it is recognized that health systems' ability to address community health needs may be limited. To better understand the interrelation between social determinants of health and health outcomes, health systems need to understand the health concerns and needs of populations. The aim of this study was to map the perceived health needs of Israel's northern periphery’s diverse ethnic and religious communities and regional clusters by conducting a community health needs assessment (CHNA). Methods The study employed a mixed-methods approach. We conducted a CHNA in the Galilee between November 2019 to January 2020 (n = 750). Additionally, we conducted focus groups using design thinking methodology to better understand the underlying causes of existing gaps between community and healthcare representatives (n = 42). Quantitative data was analyzed using multiple logistic regressions and qualitative data was analyzed using a content and thematic analysis. Results Galilee residents perceived sense of community (78%) as the major strength while cancer (53%) was perceived as the major health problem followed by heart disease and stroke (28.4%). The adjusted odds ratios for the association of each predictor with each perceived social and structural determinants of health among respondents indicated that Arab respondents were more likely to report race/ethnicity discrimination, domestic violence, lack of parks and recreation, neighborhood violence, limited places to exercise, school dropout and limited access to healthy food, as determinants affecting health than Jews. Conversely, Jews were more likely than Arabs to report access to mental health services, access to transportation, lack of job opportunities and access to a doctor's office as determinants affecting their health. Qualitative analysis revealed residents felt a 'lack of health security' as a result of problematic access to specialty and mental health services, especially for elderly populations. Conclusions CHNA can inform the design of tailored interventions that will improve health for Galilee residents addressing their socioeconomic-cultural–geographical characteristics. The study's findings raise the need to create such tailored approaches to address the lack of health security felt by residents and improve not only health services provision but the social determinants affecting their health.